1975
DOI: 10.1017/s0043174500065103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Climate and Additives on Bentazon

Abstract: Experiments were conducted in the growth chamber and greenhouse to determine the influence of humidity, temperature, simulated rainfall, and oil additives with bentazon [3-isopropyl-1H-2,1,3-benzothiadiazin-(4) 3H-one 2,2-dioxide] upon redroot pigweed (Amaranthus retroflexusL.) control. Generally, bentazon gave increased redroot pigweed control with high rather than low humidity. However, the increased weed control with high humidity was greater at 10 C than at 20 or 30 C. A simulated rainfall within 24 hr aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 3 publications
6
43
1
Order By: Relevance
“…When the RH and soil moisture were low, a pronounced 24-h oscillation in severe leaf injury was observed for leaves 1 and 2. The effects of RH or moisture on the degree of injury were consistent with those reported in other studies (Nalewaja et al 1975, Wills 1976 where, under conditions o( high moisture, the injurious effects of bentazon were more pronounced than under drier conditions (Wills 1976). The youngest leaves (No.…”
Section: Oscillation In Sensitivitysupporting
confidence: 89%
See 1 more Smart Citation
“…When the RH and soil moisture were low, a pronounced 24-h oscillation in severe leaf injury was observed for leaves 1 and 2. The effects of RH or moisture on the degree of injury were consistent with those reported in other studies (Nalewaja et al 1975, Wills 1976 where, under conditions o( high moisture, the injurious effects of bentazon were more pronounced than under drier conditions (Wills 1976). The youngest leaves (No.…”
Section: Oscillation In Sensitivitysupporting
confidence: 89%
“…The toxicity of bentazon has been positively correlated with the uptake of the material by the leaf tissue (Retzlaff and Hamm 1976). It has also been suggested that absorption may be increased by moistening the leaf surface (Nalewaja et al 1975), resulting in greater injury. These two points could explain, at least in part, the differences observed between the high and the low moisture conditions, but not the daily oscillations.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Twenty‐four hours after treatment, johnsongrass control from dalapon plus surfactant was three times greater than that provided by dalapon alone (8). Adjuvants have also been known to help overcome adverse environmental conditions and enhance toxicity under desirable environmental conditions (11).…”
Section: Temperature (Tm) Relative Humidity (Rh) and Dew (Dw) Recormentioning
confidence: 99%
“…Dew is another environmental factor that can influence herbicide efficacy. Nalewaja et al (11) concluded that dew may lead to increased uptake of herbicides. However, excess dew can lead to the herbicide being washed off, thus reducing efficacy.…”
Section: Weed Height and Environment Effect On Efficacymentioning
confidence: 99%
“…Similar results were reported by Nalewaja et al (1975) using redroot pigweed (Amaranthus retroflexus L.) and simulated rainfall of 9800 L/ha 24 hours after bentazon application. The rainfall decreased redroot pigweed control by 21% with bentazon alone, but when petroleum oil was added to the spray, the reduction was 12%, and only 7% with linseed oil.…”
Section: Effect Of Additives On Herbicide Uptakesupporting
confidence: 86%